EFFECTS OF SEED COATING USING PLANT-BENEFICIAL MICROBES ON THE GERMINATION OF Centrosema pubescens SEEDS - Handayani, Indri (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Centrosema pubescens is a legume plant that is commonly used as animal feed, cover crop, and one of the plants used to reclaim critical land. This study was conducted to increase the germination of C. pubescens seeds by coating the seeds using a coating material enriched with a consortium of microbes consisting of nitrogen-fixing bacteria, phytohormones-producing bacteria, phosphate-solubilizing bacteria, and arbuscular mycorrhizal fungi. Germination test on control, seed coating, and microbial seed coating was carried out using the top of the sand method for 28 days. Observational data were tested using ANOVA statistics and LSD tests. Results of the research showed the moisture content of the seeds was 12.45%, the purity of the seeds was 95.11% and the weight of 1000 seeds was 23.74 g. The germination test denoted that the number of normal germinated seeds in seed coating and microbial seed coating was significantly different from the control. In addition, dead seeds in microbial seed coating treatment had the lowest value and were significantly different from other treatments. These results indicate that microbial seed coating can increase seed germination and considerably reduce seed death due to seed-borne pathogens.